Praktik Toleransi Kehidupan Beragama pada Masyarakat Etnis Tionghoa di Kota Surabaya - Diba Sofinadya; Warsono Warsono (Kajian Moral dan Kewarganegaraan, 2023)
This study was written to provide an overview of the practice of religious tolerance in the Chinese ethnic community in Surabaya by using Berkson's theory, namely the theory of cultural pluralism: mosaic analogy which emphasizes freedom in culture. The method used is a qualitative research method with descriptive research and interview data collection techniques are expected to explain in detail the facts in the field. The informants in this study were 4 people who were the people of the Chinatown area who met the characteristics required by the researcher. The results of the study then prove that the practice of religious tolerance in the ethnic Chinese community in Surabaya has reached a democratic stage marked by various tolerance practices both in the family environment or in the community. The influence of the realization of good Tolerance Practices is inseparable from cultural and ethnic similarities. This practice of tolerance is manifested in the behavior of people who respect each other's religious differences, such as not arguing for a long time if there is a difference of opinion on the religion they profess. On the other hand, the tolerance applied in religion also has a significant impact on the development of society Keywords : tolerance, chinese community, religion.